An evaluation of the implementation of affirmative action : a case study, Department of the Premier, KwaZulu-Natal - Dlamini, Christophine Nombuso (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2001.